A dual-memory architecture for reinforcement learning on neuromorphic platforms. Issue 2 (9th September 2021) - Olin-Ammentorp, Wilkie; Sokolov, Yury; Bazhenov, Maxim
Abstract: Reinforcement learning (RL) is a foundation of learning in biological systems and provides a framework to address numerous challenges with real-world artificial intelligence applications. Efficient implementations of RL techniques could allow for agents deployed in edge-use cases to gain novel abilities, such as improved navigation, understanding complex situations and critical decision making. Toward this goal, we describe a flexible architecture to carry out RL on neuromorphic platforms. This architecture was implemented using an Intel neuromorphic processor and demonstrated solving a variety of tasks using spiking dynamics. Our study proposes a usable solution for real-world RL applications and demonstrates applicability of the neuromorphic platforms for RL problems.